Zoonotic Sporotrichosis outbreak: Emerging public health threat in the Amazon State, Brazil. - Viviany Araujo Mesquita; Sinesio Talhari; André Luiz Leturiondo; Guilherme Caldas de Souza; Euzenio Moreira de Brito; Suanni Lemos de Andrade; Débora Cristina de Lima Fernandes; Maria Zeli Moreira Frota; Rossilene Conceição da Silva Cruz; Juliana de Andrade Rebouças Guimarães; Helio Amante Miot; Carolina Talhari; et al. (Public Library of Science (PLoS), 2024)
Background Sporotrichosis is the most common subcutaneous mycosis caused by Sporothrix spp. Traditionally, it is transmitted through injuries involving plant debris. However, over the past few decades, there has been an epidemic increase in human cases resulting from contact with infected animals, particularly cats, in various regions of Brazil. In this report, we report a notable increase in both human and animal cases within the Brazilian Amazon state. Methodology/principal findings An ecological study was conducted by analyzing official records of human and animal sporotrichosis diagnosed in the state of Amazon from 2020 to 2023. Data including patient demographics, clinical manifestations, mycological examination results, and species identification through PCR confirmation were evaluated. During this period, a total of 950 human cases and 2,823 animal cases of sporotrichosis were reported at an exponential rate, since no human cases were registered in 2020. The spatial and temporal dispersion of human sporotrichosis followed that of animal cases, moving from downtown areas to the periphery. Contact with infected animals was reported in 77.7% of cases, with cats being the most commonly implicated (73.5%). Only 66.7% of individuals underwent mycological examination. Among the positive cultures for Sporothrix spp., 65.4% were identified as S. brasiliensis. All patients were treated with systemic antifungals. Conclusions/significance This study highlights a rising incidence of sporotrichosis among animals and humans in the Brazilian Amazon region over the past four years, with S. brasiliensis being the predominant agent. Collaborative efforts involving healthcare professionals, veterinarians, and public health authorities are crucial to implement effective control measures, educate populations at risk, and promote responsible guidance for pet guardians. These measures are essential to mitigate the burden of epidemic sporotrichosis in Brazil.